Implementation and Validation of the 2013 Caprini Score for Risk Stratification of Arthroplasty Patients in the Prevention of Venous Thrombosis. (3rd April 2019) - Krauss, Eugene S.; Segal, Ayal; Cronin, MaryAnne; Dengler, Nancy; Lesser, Martin L.; Ahn, Seungjun; Caprini, Joseph A.
Appropriate chemoprophylaxis choice following arthroplasty requires accurate patient risk assessment. We compared the results of our prospective department protocol to the Caprini risk assessment model (RAM) retrospectively in this study group. Our goal was to determine whether the department protocol or the Caprini score would identify venous thromboembolism (VTE) events after total joint replacement. A secondary purpose was to validate the 2013 Caprini RAM in joint arthroplasty and determine whether patients with VTE would be accurately identified using the Caprini score. A total of 1078 patients met inclusion criteria. A Caprini score of 10 or greater is considered high risk and a score of 9 or less is considered low risk. The 2013 version of the Caprini RAM retrospectively stratified 7 of the 8 VTE events correctly, while only 1 VTE was identified with the prospective department protocol. This tool provided a consistent, accurate, and efficacious method for risk stratification and selection of chemoprophylaxis.